Breast cancer awareness among undergraduate medical students in a tertiary healthcare centre in Mangalore, India - Joy, Nitu; D’Souza, Caren; D’Souza, Clement R. S. (International Surgery Journal, 2018)
Background: Breast cancer is currently one of the leading causes of cancer related deaths in India. Early detection of breast cancer can improve the survival rates. The aim of this study was to assess the breast cancer awareness among undergraduate medical students in a tertiary healthcare centre in Mangalore, India. This was an observational study conducted among 95 medical students from first to final year in a tertiary healthcare centre. Methods: Data was collected using a standard self-administered questionnaire. Participants were given printed copies of the questionnaire and were given time to fill their responses in a confidential setting. Participants were then asked to return these questionnaires anonymously. Statistical analysis used- Frequency distribution statistics. Results: All the participants had good knowledge about breast cancer and 78.94 % had good overall awareness about Breast self-examination (BSE). 88.42 % of the participants believed that breast cancer is curable. 75.78 % of the participants knew the technique of performing BSE and around 98.93% agreed that BSE is important. Almost all the participants (98.94%) stated that Breast self-examination, Clinical breast examination and Mammogram can detect breast cancer. Conclusions: To improve the breast cancer awareness in the community, more effective health education programmes will be required to enlighten healthcare professionals as well as the general public regarding the risk factors, early detection and management of breast cancer.